1972
DOI: 10.1002/cpt1972136861
|View full text |Cite
|
Sign up to set email alerts
|

The clinical pharmacology of oral and inhaled salbutamol

Abstract: The clinical pharmacology of 3H-salbutamol has been investigated in 12 asthm Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
26
2
1

Year Published

1974
1974
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(37 citation statements)
references
References 6 publications
7
26
2
1
Order By: Relevance
“…Dollery (1973) reported that the picture after administration directly into the lung was different, confirming the hypothesis that the majority of the aerosol dose is swallowed. A similar pattern has been described following the administration of salbutamol (Evans, Paterson, Richards & Walker, 1971;Walker, Evans, Richards & Paterson, 1972).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Dollery (1973) reported that the picture after administration directly into the lung was different, confirming the hypothesis that the majority of the aerosol dose is swallowed. A similar pattern has been described following the administration of salbutamol (Evans, Paterson, Richards & Walker, 1971;Walker, Evans, Richards & Paterson, 1972).…”
Section: Discussionsupporting
confidence: 70%
“…Excluding patient W.W. whose baseline FEV1 was 100% of predicted normal (Table 1), the mean FEVy before treatment was 1.2 litres and the average percentage rise following salmefamol was 44%. In a study where 4 mg oral salbutamol was given to asthmatic patients, peak levels of free drug associated with bronchodilatation were 42-54 nM (Walker et al, 1972). The patients in that study were comparable with those in the present study, their mean baseline FEV1 before salbutamol was 1.5 litres and the average percent rise above baseline was 45%.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Systemic absorption of inhaled salbutamol may occur following deposition in the lungs and oropharynx, and also from the gut after swallowing. Direct systemic absorption from the buccal mucosa should avoid first-pass metabolism by sulphate conjugation (Walker et al, 1972;Morgan et al, 1986;Goldstein et al, 1987). Kung et al (1987) showed that mouth washing has no effect on systemic ,B-adrenoceptor responses to salbutamol 1 mg given by MDI.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in systolic blood pressure produced by salbutamol has been reported previously (Corea et al, 1984) although other authors have shown a fall (Mc Devitt et al, 1975) or no change (Walker et al, 1972;Watson & Richens, 1974). Salbutamol has been shown to improve indices of myocardial contractility (Sharma & Goodwin, 1978;Bourdillon et al, 1980) although it is not clear if this is due to a positive inotropic effects or a reduction in afterload caused by vasodilation.…”
Section: Discussionmentioning
confidence: 91%